Evidence for decreasing sperm count in African population from 1965 to 2015 - Sengupta, Pallav; Nwagha, Uchenna; Dutta, Sulagna; Krajewska-Kulak, Elzbieta; Izuka, Emmanuel (African health sciences, 2017)
Purpose: This meta-analysis, following our previous reports those documented an overall 57% diminution in mean sperm concentration around the globe over past 35 years and 32.5% decline in past 50 years in European population, attempts to report the declining trend of sperm concentrations in African population between 1965 and 2015. Methods: In the course of retrieval of data following MOOSE guidelines and PRISMA checklist, we found a total of fourteen studies that have been conducted during that period on altering sperm concentration in the African male. Results: Following analysis of the data, a time-dependent decline of sperm concentration (r = -0.597, p = 0.02) and an overall 72.6% decrease in mean sperm concentration was noted in the past 50 years. The major matter of concern is the present mean concentration (20.38×106/ml) is very near to WHO cut-off value of 2010 of 15×106/ml. Several epidemic diseases, genital tract infection, pesticides and heavy metal toxicity, regular consumption of tobacco and alcohol are reported as predominant causative factors. Conclusion: This comprehensive, evidence-based meta-analysis and systematic review concisely presents the evidence of decreased sperm concentration in the African male over past 50 years with possible causative factors to serve the scientific research zone related to male reproductive health.